The forms, Drivers, and Impacts of Corporate Entrepreneurship in Business Organizations - Suhartanto, Eko (Universitas Prasetiya Mulya, 2025)
This literature review analyzes entrepreneurship and corporate entrepreneurship, focusing on their roles in economic development and organizational transformation. Entrepreneurship is categorized into the effects of entrepreneurial activities, the causes driving entrepreneurship, and the processes involved. Corporate entrepreneurship, defined as entrepreneurial activities within established firms, aims to tackle challenges from dynamic external factors like technological changes and competition. Corporate entrepreneurship manifests through corporate venturing and strategic entrepreneurship, leveraging resources and fostering innovation for a competitive advantage. The review discusses key antecedents like organizational culture and strategic leadership that influence success, with outcomes extending to financial performance and non-financial impacts such as stakeholder satisfaction and risk reduction. Aligning corporate entrepreneurship with broader strategic goals is crucial in dynamic environments. Entrepreneurial orientation, characterized by risk-taking, proactiveness, and innovativeness, fosters a corporate entrepreneurial culture. The study underscores the need for further research into corporate entrepreneurship's influence on organizational success amidst changing external conditions.